2003
DOI: 10.1021/ja029297m
|View full text |Cite
|
Sign up to set email alerts
|

Ring-Opening Reaction of Phosphorus-Bridged [1]Ferrocenophane via Ring Slippage from η5- to η-Cp

Abstract: A reaction mechanism was investigated for a ring-opening reaction of RP(E)-bridged [1]ferrocenophane, where RP(E) = PhP(S) (3a), PhP (3b), and MesP (3c) (Mes = 2,4,6-trimethylphenyl). Irradiation of UV-vis light in the presence of an excess amount of P(OMe)(3) transformed 3a to [Fe(PhP(S)(eta(5)-C(5)H(4))(eta(1)-C(5)H(4)))(P(OMe)(3))(2)] (4a), in which one of the two cyclopentadienyl (Cp) rings of 3a changed its coordination mode from eta(5) to eta(1) and vacant coordination sites thus formed on the iron cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 29 publications
2
48
0
1
Order By: Relevance
“…[92] The molecular structure of the product was determined by Xray crystallography and revealed an h 5 !h 1 haptotropic shift.…”
Section: Polyferrocenylsilanesmentioning
confidence: 99%
“…[92] The molecular structure of the product was determined by Xray crystallography and revealed an h 5 !h 1 haptotropic shift.…”
Section: Polyferrocenylsilanesmentioning
confidence: 99%
“…Later, the same group reported the photolytic ROP 2 PPh}] when irradiated by UV light in THF at 0 8C, through a M À Cp bond cleavage mechanism affording PFPs with a broad molecular weight distribution (Scheme 1b). [16] In the work described, no externally added initiator was used and the polymerization was non-living with no control of molecular weight.…”
Section: Introductionmentioning
confidence: 99%
“…Photolytic ROP of phosphorus-bridged [1]ferrocenophanes. [15,16] Scheme 2. Mechanism for the photolytic polymerization of silicon-bridged [1]ferrocenophanes (S = solvent, for example, THF; * = photoexcited monomer).…”
Section: Introductionmentioning
confidence: 99%
“…[12] Miyoshi and co-workers have demonstrated that strained phospha [1]ferrocenophanes (a % 278) undergo unprecedented Fe À Cp bond cleavage upon photoirradiation and, in the presence of donor solvents such as THF, photolytic ROP was detected. [45,46] [47,48] In addition, in the presence of phosphorus-donor ligands sila [1]ferrocenophanes have been shown to undergo reversible haptotropic shifts of the Cp ligand from h 5 to h 1 on phosphine coordination. [49] The subtle dependence of the reactivity of [1]ferrocenophanes on the nature of the bridging atom is demonstrated by the following example: whereas the aforementioned treatment of bora [1]ferrocenophanes 5 with metal carbonyls leads to reactivity at the FeÀCp bond to yield 6 and 7, [12] the analogous reaction using tin-bridged [1]ferrocenophanes yields products arising from the insertion of metal carbonyl fragments into the Sn À Cp bond.…”
Section: Introductionmentioning
confidence: 99%